THEORETICAL AND PRACTICAL DIFFICULTIES IN THE TRANSLATION OF NEOLOGISMS - Ubaydullayeva, Madina Baxtiyorovna (INTERNATIONAL CONFERENCES, 2023)
This article discusses the possible problems in translating neologisms. Neologisms are the new words which enter the language vocabulary recently. These words are sometimes difficult to translate into the target language due to some factors. This article shows some of these factors and ways of translation.